The MAP Kinase Pmk1 and Protein Kinase A Are Required for Rotenone Resistance in the Fission Yeast, Schizosaccharomyces pombe - Wang, Yiwei (2010)
Rotenone is a widely used pesticide that induces Parkinson's disease-like symptoms in rats and death of dopaminergic neurons in culture. Although rotenone is a potent inhibitor of complex I of the mitochondrial electron transport chain, it can induce death of dopaminergic neurons independently of complex I inhibition. Here we describe effects of rotenone in the fission yeast, Schizosaccharomyces pombe, which lacks complex I and carries out rotenone-insensitive cellular respiration. We show that rotenone induces generation of reactive oxygen species (ROS) as well as fragmentation of mitochondrial networks in treated S. pombe cells. While rotenone is only modestly inhibitory to growth of wild type S. pombe cells, it is strongly inhibitory to growth of mutants lacking the ERK-type MAP kinase, Pmk1, or protein kinase A (PKA). In contrast, cells lacking the p38 MAP kinase, Spc1, exhibit modest resistance to rotenone. Consistent with these findings, we provide evidence that Pmk1 and PKA, but not Spc1, are required for clearance of ROS in rotenone treated S. pombe cells. Our results demonstrate the usefulness of S. pombe for elucidating complex I-independent molecular targets of rotenone as well as mechanisms conferring resistance to the toxin.